Dissemination Technology For Small-Medium Scale Enterprise - Musa Hubeis (Universitas Trisakti, 2005)
Small-medium scale enterprises enterprises (SME) found in developing and developed countries is still facing classical handicap such as technology, finance, managerial and market accessibility, in spite of its high flexibiliry, responsiveness, dynamic and resistance. Therefore, designing and management of SME in context of technology dissemination needs to understand business dimension as enterprise description, product/service, market, enterprise location, competition, management, personnel, budget, research and development. Beside general technology, both SME in general and specific are closely related to: (1) Technology choice covering technology complexities, capital intensity, and human resource (HR) quality; (2) Technology learning strategy based on learned technology position combination, both process and products with faced competition, through existing learned technology, technology integration, technology development and basic research; (3) Enterprise unit covering enterprise scale, HR, organization,location, product type, enterprise unit, experiences, competition level and business network; (4) Performance indication of business unit and business man, and technology diffusion institutions; (5) Linkages of business with characteristics of authority, functional, normative and diffusion. Dissemination pattern of integrated and sustainable technology is expected to establish network among development subjects intensively and dynamically, to compile agenda of transfer technology, implement technology that is appropriate and develop learning organization for technology dissemination activities.